Pengaruh Penerapan Model Radec dalam Pembelajaran Membaca Buku Fiksi Terhadap Kemampuan Berpikir Kreatif Siswa - Boenga Jenny Hendrianty, Boenga Jenny Hendrianty; Rika Nurbayanti, Rika Nurbayanti; Novi Nawangsih, Novi Nawangsih; Wahyu Sopandi, Wahyu Sopandi; Hisny Fajrussalam, Hisny Fajrussalam (Jurnal Didaktika Pendidikan Dasar, 2025)
Creative thinking is an important skill in facing global challenges, but it receives less attention in learning.This study aims to analyze the extent to which the habit of reading non-textbook fiction influences the development of creative thinking skills in elementary school students by integrating the RADEC learning model into the instructional process. The methodology employed in this research involves a quantitative approach and a quasi-experimental design. The study population consists of all third-grade students at SDN Sukarasa 01, Bogor Regency. Data on students' creative thinking skills were collected using open-ended tests. The t-test statistical analysis showed a significant difference in creative thinking skills between students taught using the RADEC model and those receiving Direct Instruction. The significance value (Sig. two-tailed) was < 0.001. An average N-gain score of 0.60 indicates a moderate improvement in creative thinking. Simple linear regression revealed that the RADEC model contributed 48.9% to students’ creative thinking enhancement. These results have meaningful implications in education, especially in meeting 21st-century demands for higher-order thinking. The RADEC-based approach offers an effective way to boost students’ cognitive skills, particularly in generating original ideas, flexible thinking, and solving problems creatively. The habit of reading non-textbook fiction is viewed as a potential driver in enriching imagination and nurturing creative thought patterns, making it worth exploring in future studies.